2000
DOI: 10.1074/jbc.275.14.10009
|View full text |Cite
|
Sign up to set email alerts
|

Solution Structure and Backbone Dynamics of Long-[Arg3]insulin-like Growth Factor-I

Abstract: Long-[Arg 3 ]insulin-like growth factor-I (IGF-I) is a potent analog of insulin-like growth factor-I that has been modified by a Glu

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

3
32
0

Year Published

2001
2001
2023
2023

Publication Types

Select...
5
2
1

Relationship

3
5

Authors

Journals

citations
Cited by 24 publications
(35 citation statements)
references
References 33 publications
3
32
0
Order By: Relevance
“…Similarly, the general fold of free IGF-I reported in NMR solution studies [19][20][21] was preserved in the crystal complex [17]. Although the structures were highly defined for most residues, less definition in the crystal structure of IGF-I was seen for residues 1-6, 31-40 (which form a solvent exposed loop) and 62-67 [17], which is consistent with NMR data in those regions [19][20][21].…”
Section: Structural Evidence For Igfbp Residues Involved In the Igfbpsupporting
confidence: 85%
“…Similarly, the general fold of free IGF-I reported in NMR solution studies [19][20][21] was preserved in the crystal complex [17]. Although the structures were highly defined for most residues, less definition in the crystal structure of IGF-I was seen for residues 1-6, 31-40 (which form a solvent exposed loop) and 62-67 [17], which is consistent with NMR data in those regions [19][20][21].…”
Section: Structural Evidence For Igfbp Residues Involved In the Igfbpsupporting
confidence: 85%
“…The binding curve at pH 3·4 was atypical of the high-affinity binding interaction with IGFBP-2, showing more rapid dissociation from IGF-I biosensor surfaces than at pH 4·4 or 5·4. Furthermore, TROSY spectra of the complex at various pH values in (Laajoki et al 2000) and IGF-II (Torres et al 1995) are shown in stereo. The backbone is shown as a ribbon and the side chains as lines.…”
Section: Discussionmentioning
confidence: 99%
“…In this case, the aryl azide resides near the outer edge of the IGF-1-binding domain, defining the site of contact for Gly 1 . The longer, more flexible side chain present on the aryl azide in bedG 1 IGF-1 has the potential to define a contact site within the vicinity of the other residues of the IGFBPbinding domain, including Glu 3 , which plays an essential role in maintaining high affinity binding to the IGFBPs (43). Although we cannot rule out the possibility that this side chain results in the labeling of regions of the IGFBPs outside the IGF-binding domain, we believe that the likelihood of this occurring is minimal based on the previous identifications of C-terminal binding activity described above.…”
Section: Discussionmentioning
confidence: 99%